2003
DOI: 10.1016/s0006-3207(02)00153-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and local population structure of fragmented populations of Trillium camschatcense (Trilliaceae)

Abstract: Trillium camschatcense, a long-lived common woodland herb, has been experiencing intensive habitat fragmentation over the last century in eastern Hokkaido, Japan. We examined the genetic diversity and population genetic structure of 12 fragmented populations with different population sizes using allozyme electrophoresis. The percentage of polymorphic loci and mean number of alleles per locus were positively related to population size, probably due to the stochastic loss of rare alleles (frequency of q <0.1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 49 publications
2
54
1
2
Order By: Relevance
“…Contrary to the T. camschatcense investigation (Tomimatsu and Ohara, 2003) and to our expectations, our study did not reveal a significant relationship between the size of T. reliquum populations and genetic variation. Population genetics theory predicts that larger populations are more likely to have higher heterozygosity and greater allelic richness.…”
Section: Genetic Diversity Within Populationscontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the T. camschatcense investigation (Tomimatsu and Ohara, 2003) and to our expectations, our study did not reveal a significant relationship between the size of T. reliquum populations and genetic variation. Population genetics theory predicts that larger populations are more likely to have higher heterozygosity and greater allelic richness.…”
Section: Genetic Diversity Within Populationscontrasting
confidence: 99%
“…However, even in perennial herbs with widely disjunct populations, for example Tradescantia hirsuticaulis (Godt and Hamrick, 1993) a granite outcrop endemic with a similar geographic range to T. reliquum, or Sarracenia leucophylaf (Wang et al, 2004), another relatively rare southeastern perennial herb, such extreme population variability in genetic diversity is uncommon. In contrast, Tomimatsu and Ohara (2003) reported comparable levels of both species and population genetic diversity in Trillium camschatcense in eastern Hokaido, Japan. In their study area, previously large, continuous populations had been fragmented into smaller remnants.…”
Section: Genetic Diversity Within Populationsmentioning
confidence: 82%
See 1 more Smart Citation
“…Firstly, it was probably closely connected with its small population size and habitat fragmentation. The theory of population genetics indicates that genetic differentiation caused by genetic drift and inbreeding depression should increase in progressively smaller and isolated populations (Templeton et al 1990), as supported by previous reports (Buza et al 2000;Shea and Furnier 2002;Tomimatsu and Ohara 2003). Despite its wide geographic distribution, the habitats of P. pseudocerasus were fragmented into small patches largely due to geographic barriers and anthropogenic activities, and the sizes of the isolated populations, e.g.…”
Section: Genetic Structurementioning
confidence: 53%
“…Experimental and field investigations have demonstrated that fragmented populations may lose allelic richness or genetic diversity, and have increased population differentiation due to genetic drift and inbreeding depression (e.g. Buza et al 2000;Tomimatsu & Ohara 2003). Thus, an accurate estimate of the level and distribution of genetic diversity of threatened and endangered species is an important element in designing conservation programmes (Smith & Wayne 1996;Höglund 2009).…”
Section: Introductionmentioning
confidence: 99%